Effectiveness of AI Integration into Computer-Assisted Language Learning (CALL) on Student Writing Skills Based on Gender - Fazal, Namra; Tahir, Muhammad Shoaib; Chaudhary, Mahnoor; Abbasi, Minahil (Pakistan Journal of Humanities and Social Sciences, 2024)
This research has evaluated the efficacy of AI in CALL to improve writing among students by gender. The analysis involved a literature review on how AI and processing have made an impact on writing and it’s utilized to augment writing of the English language learners. It has reviewed an inspection of how educational technology affects men and women disparately. The result proved that integrating AI in technology enhances writing quality of language learners, regardless of their sex. It has exposed the nitty-gritty of gender, technology use and its effectiveness. It stipulates that in the imbuing of CALL on the basis of student demographics, gender-tailored approaches are essential. Moreover, policies and interventions in CALL, need to accommodate gender discrepancies to allow for maximum effectiveness. It is also crucial to delve more deeply into the after-effects of AI infused CALL over time, such as constructing intervention tools attuned with genders. Also, inspecting the fine-tuned effects of integrating AI on student writing, over longer periods would yield insights, into fashioning optimal CALL strategies, suited to learner populations.